Photoshop CS5 the missing manual - Snider, Lesa (The missing manual, 2010)
Photoshop CS5 is more amazing than ever, but it can be overwhelming if you're just getting started. This book makes learning Photoshop a breeze by explaining things in a conversational, friendly style -- with no technical jargon. After a thorough introduction to the program, you'll delve deep into Photoshop's secrets with expert tips and practical advice you can use every day. Learn your way around. Get a guided tour of Photoshop's efficient new workspaceUnlock the power. Learn the best ways to use layers, channels, masks, paths, and moreBring images to life. Discover how to effectively retouch.